The Catocala naganoi species group (Lepidoptera: Noctuidae), with a new species from Vietnam - Kons, Hugo L. Jr.; Borth, Robert J.; Saldaitis, Aidas; Didenko, Sergei (Zootaxa, 2017)
The Asian Catocala naganoi species group is delimited and reviewed, with a diagnosis of the constituent species based on genitalic, wing pattern, and COI 5’ mtDNA characters. The included species are Catocala naganoi Sugi, 1982, C. solntsevi Sviridov, 1997, C. naumanni Sviridov, 1996, and C. katsumii sp. n. which is described here as new.